On the contribution of internal variability and external forcing factors to the Cooling trend over the Humid Subtropical Indo-Gangetic Plain in India. Issue 1 (December 2018) - Nath, Reshmita; Luo, Yong; Chen, Wen; Cui, Xuefeng
Abstract The summer surface air temperature (SAT) in the Humid Subtropical Climate Zone in India, exhibits a significant cooling trend ( − 3 °C/40 yrs.) in CRU observational data during 1961– 2000. Here we investigate the contribution of internal and external factors, which are driving this cooling trend. Using the Community Earth System Model-Large Ensemble (CESM-LE), we analyze the historical climate change in presence of internal climate variability. Most of the model ensemble members could reproduce this amplified cooling (<−3 °C) as shown from CRU data. Further analyses reveals that external forcing displays a strong cooling effect over this region, while internal variability displays mixed cooling (in most cases) and warming signals. The signal to noise ratio i.e. the ratio of external forcings and internal climatic variability is less than 1, which indicates that internal climatic variability dominates over the forced response. Furthermore, to quantify the role of different external forcing factors we used the CCSM4 single forcing simulations. The simulation results from CESM-LE and CCSM4 suggest that the cooling trend over the region is primarily due to the combined influence of internal variability ( 73%) and partly due to aerosol ( 10%) and ozone only forcing, which strongly mask the warming effect of GHG and solar forcing.